1990
DOI: 10.1007/bf03170571
|View full text |Cite
|
Sign up to set email alerts
|

Contrast information of digital imaging in laser film digitizer and display monitor

Abstract: A lO-bit or 12-bit grey scale is provided in commercial laser film digitizers. The true contrast resolution on the digitized image within a laser spot area of 200 #m in diameter is limited by both the quantum mottle and instrumentation noise. In this report, we investigated the mean value, standard deviation, and adjacent pixel correlation coefficient on a calibrated step wedge film with two laser digitizers. The results were disappointing, because we found that the evaluated contrast information is inferior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The general approach taken to assess the signal, noise, and density range performance of the digitizers involved four steps, and is similar to that used in previous reports. [2][3][4][5][6][7] First, a step-wedge test film was created. Second, the test film was digitized using the four CCD-based units, and one laser film digitizer.…”
Section: Methodsmentioning
confidence: 99%
“…The general approach taken to assess the signal, noise, and density range performance of the digitizers involved four steps, and is similar to that used in previous reports. [2][3][4][5][6][7] First, a step-wedge test film was created. Second, the test film was digitized using the four CCD-based units, and one laser film digitizer.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have found that the contrast resolution of a display is often substantially less in practice than that specified by the manufacturer. 26 In telemedicine applications based on videoconferencing, the picture rate is a factor and so too is the quality of sound.…”
Section: Information Displaymentioning
confidence: 99%
“…3Y7 Other works attempt to calibrate film digitizers with respect to gray scale monitors, but did not have an accepted standard to base their results on. 8,9 The goal of this work is not to establish a quality control parameter, but to present a methodology to provide lookup tables (LUT) to individual images. These LUTs will transform the pixel values of the image data sets so that the luminance of displayed images will be equivalent to the original films as observed on a viewbox as defined by the GSDF.…”
Section: Introductionmentioning
confidence: 99%